Recommendations on Implementing the Model of Business Reputation (Goodwill) Management at the Industrial Enterprises - O. I. Kalinskiy (Управленческое консультирование)
The problem of effective management of the intangible assets is quite serious in the circumstances when the rapid information flow  about the functioning of any company (industrial enterprise) may  alter its market value quite fast. Chief among the intangible assets is business entity’s reputation that is manifested as goodwill in various  cases on the entity’s balance sheet. The system of managing  business reputation created by the author must be transpired into  the mission, tasks and KPIs of the management team in order to  both improve the reputation and increase the market value of the entity. Materials & Methods: the holistic model of the quantitative management of the enterprise’s reputation (goodwill) developed by  the author includes: 1) managing of the reputation by influencing the structure of value added (profit, amortization and  salary); 2) managing of the enterprise’s business reputation via  influencing the structure of capital (whereas π1 — is the ratio of current assets to total assets and π2 — the indicator of the  enterprise’s cover with the own and long term credits and 3)  managing of goodwill based on the rating valuation utilizing the  financial coefficients. This model of the quantitative valuation of  goodwill carries scientific value and is the product of author’s long  term research. In the work the author also presents the organizational chart of carrying out calculations to manage business  reputation of the enterprise with the detailed description of five steps for management in the public company (from collection and  preparation of data about market value of the company and its  goodwill to confirmation of the action plan with the participants of  the process and enterprise’s top officials to manage goodwill in the long-term).Results: the author describes in detail management actions targeted at enhancing the business reputation depending on the  value added characteristics and on the capital structure, namely  decreasing or increasing of salaries; increasing or decreasing the  value of amortization; increasing or decreasing the size of current  assets or short term debt). The author also highlights potential conflicts among various departments of the enterprise  while managing the business reputation and outlines potential  solutions to these conflicts through the creation of the formalized  internal system of mitigation and reaching the agreement.Discussion & Conclusions: the result of the conducted research is the adaptation of a unique model of its quantitative valuation of  business reputation with its subsequent management to enhance market value of the whole company via increase in value  added and improvement of the capital sctructure.